Guatemala implements climate services for agriculture at national scale - CGIAR Research Program on Climate Change, Agriculture and Food Security (2019)
With strengthening and establishment of new LTACs, compiled evidence show a institutional transformation of INSIVUMEH in Guatemala. Changes are related with (i)development of climate information production focused in local information demand, (ii)transferring knowledge to stakeholders and farmers communities, (iii)the creation of the national agro-climatic bulletin addressing the demand of agricultural stakeholders, (iv)promoting agreements for scaling-up of LTAC, and (v)enhanced capacity to co-create and coordinate climate services acquiring new skills needed to improve the information generated for agriculture .